A Study on the Fluorescence Properties of New Laser Material-n-B18H22 in SDS Aqueous Solution. (2nd May 2019) - Zhang, Lin-Na; Chen, Jie; Huang, Xu-Guang; Meng, Hong-Yun; Tan, Chun-Hua
Abstract : The effect of anionic surfactant sodium dodecyl sulfate (SDS) on the fluorescence ofn -B18 H22 was studied. The experimental result revealed that the fluorescence ofn -B18 H22 was obviously enhanced with the increase of the concentration of SDS, mainly due to the hydrophobic protection ofn -B18 H22 by SDS. Under the optimum conditions, the fluorescence intensity was proportional to the concentration ofn -B18 H22 in the range of 0-8.0×10 −3 mol·L −1 and 8.0×10 −3 mol·L −1 -3.3×10 −2 mol·L −1, respectively. It was observed that a break appeared in the curve of fluorescence intensity with surfactant concentration. The critical micelle concentration (CMC, 7.9×10 −3 mol·L −1 ) of SDS was obtained from this break point in a good agreement with the reported value. The fluorescence intensity increased initially with time and gradually stabilized. The results form the basis for further study of the properties and application ofn -B18 H22 in SDS solutions.